Base-promoted direct and highly selective alkynylation of electron-deficient octafluorotoluene1. Issue 40 (7th May 2015) - Liu, Cuibo; Zhao, Hui; Zhao, Haitao; Wang, Zhifang; Zhang, Bin
<x xml:space="preserve">Abstract</x> Experimental and theoretical studies are reported on the base-promoted direct alkynylation of octafluorotoluene via highly selective C–F bond cleavage.